UTILITY ACCRUAL OBJECT DISTRIBUTION IN MPSOC REAL-TIME EMBEDDED SYSTEMS - Ellisa Wulan Oktavia; Nadia Istamala; Adityanto Adityanto; Uni W Sagena; Masjaya Masjaya (LPPM Politeknik Pratama, 2024)
This study examines the impact of relocating Indonesia's capital city from Jakarta to East Kalimantan on the local economy, workforce, and associated challenges. Using qualitative methods and descriptive analysis, the findings reveal positive effects such as increased investments and economic growth driven by new infrastructure and heightened economic activity in property, hospitality, and transportation sectors. However, challenges like rising property prices, gentrification, and social changes demand sustainable spatial planning and effective social impact management. Proposed mitigation strategies include thorough planning, social infrastructure development, local economic empowerment, and regular impact monitoring. The capital relocation has the potential to boost local economic growth if managed effectively.